Environmental life cycle assessment of concrete containing biomass fly ash - Teixeira, Elisabete Rodrigues (2016)
Concrete production sector is challenged by attempts to minimize the consumption of raw materials and energy and to reduce environmental impact. The use of end-of-life products as cement replacement can allow the production of concrete with the same durability, similar quality properties and with improved environmental performance. This work studies the environmental benefits of incorporating different percentages of two types of fly ashes that can be used in concrete as cement replacement, according to the Portuguese context. The results showed that both ashes provide a benefit for the concrete production because it is possible to produce concrete with low Portland cement content and with a better environmental performance while achieving satisfactory mechanical resistance. As already demonstrated for coal fly ash, the use of biomass fly ash seems to be a promising alternative for the replacement of Portland cement.